Potential secondary metabolite analysis of soil Streptomyces sp. GMR22 and antibacterial assay on Porphyromonas gingivalis ATCC 33277 - Hera Nirwati; Ema Damayanti; Eti Nurwening Sholikhah; . Mustofa; Jaka Widada (Universitas Gadjah Mada, 2022)
Infectious diseases caused by oral pathogenic bacteria are currently a serious problem due to the increasing incidence of antimicrobial resistance. Streptomyces sp. GMR22, a soil actinobacterium which has large-genome size. In previous studies, it was known to have antifungal, and antibiofilm activity on Candida albicans. However, its antibacterial activity on oral pathogenic bacterium, Porphyromonas gingivalis is not clear. This study aimed to identify potential active compound based on genome mining analysis and to evaluate the antibacterial activity of GMR22 extract on P. gingivalis ATCC 33277. Potential active compounds and biosynthesis gene clusters were analysis using antiSMASH version 5. Antibacterial activity assay was carried out by the microdilution method on P. gingivalis ATCC 33277. Based on genome mining analysis polyketide synthase (PKS), the Streptomyces sp. GMR22 is the abundant BGCs (35%) and has large-predicted compounds which have antibiotic-antibacterial activity (22.9%). On antibacterial assay, chloroform extract of GMR22 at 7.8 – 62.5 µg/mL has high antibacterial activity on P. gingivalis compared to other extracts. Soil Streptomyces sp. GMR22 bacterium has biotechnological potential to produce active compounds for antibacterial.